PERGESERAN BAHASA DAERAH KOLONCUCU KE BAHASA MELAYU TERNATE DI MASYARAKAT KELURAHAN TOBOLE (SUATU TINJAUAN SOSIOLINGUISITIK) - Kien, Nurul Inayah; Abdullah, Taib; Abasa, Rafik M.; Mugrib, Nuz Chairul (Universitas Khairun, 2025)
This research raises the issue of the shift of koloncucu regional language that occurs in the social sphere in the Toboleu village community. This research aims to find out the shift of koloncucu regional language to Ternate Malay language and the factors that influence the occurrence of the language shift. The method in this study uses a qualitative approach with descriptive research. In this study, two stages of research were used, namely: 1) data collection through observation, interview, documentation, while data analysis is done by the process of data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that Koloncucu regional language has shifted to Ternate Malay language because some of the most dominant factors are the main causes of the shift of Koloncucu regional language to Ternate Malay language, namely migration factors and educational factors. The migration factor is that many people from other areas who are Ternate Malay speakers migrate to Toboleu village and the population exceeds the original community of the village. Educational factors are often also the cause of language shifts, because schools always introduce a second language to their students who are originally monolingual, become bilingual and eventually leave or shift the first language.